Психологія духовного становлення молодого викладача - Жигайло, Наталія (Видавництво Львівської політехніки, 2012)
Автором предложены механизмы формирования духовных ценностей личности молодого преподавателя, представлена авторская модель духовного становления личности; разработаны психологический тренинг формирования духовности молодого преподавателя. The author proposes mechanisms of spiritual values formation of a young teacher’s individuality, presents a model of spiritual identity formation, and develops psychological training of young teachers’ spiritual identity formation.
Психология духовного становления молодого преподавателя
Psychology of нoung teacher’s spiritual formation
Keywords: духовность; духовное становление; авторская модель духовного становления молодого преподавателя; психологический тренинг; критерии духовности; источники духовности; spirituality; spiritual becoming; author’s model of a young teacher spiritual becoming; psychological training; criteria of spirituality; sources of spirituality